2019
DOI: 10.4191/kcers.2019.56.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Molding Pressure and Sintering Temperature on Properties of Foamed Glass without Blowing Agent

Abstract: A process of fabricating the foamed glass that has closed pores with 8 ~ 580 µm sizes without a blowing agent by sintering 10 µm boron-free glass powder composed of CaO, MgO, SO 3 , Al 2 O 3-83 wt% SiO 2 at a molding pressure of 0 ~ 120 MPa and a sintering temperature of 750 ~ 1000 o C was investigated. To analyze the glass transition temperature of glass powder, thermogravimetric analysis-differential thermal analysis (TGA-DTA) method were used. The microstructure and pore size of foamed glass were examined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Figure 6 shows the thermal conductivity relative to the basalt-fiber addition amount. This verified that thermal conductivity increases with greater addition of basalt-fiber because the thermal conductivity of basalt-fiber, 0.8 W/m•K [13], is comparatively higher than that of foam glass, 0.115 W/m•K [14]. Thus, an increase in basalt-fiber addition results in an increase in thermal conductivity.…”
Section: Resultssupporting
confidence: 58%
“…Figure 6 shows the thermal conductivity relative to the basalt-fiber addition amount. This verified that thermal conductivity increases with greater addition of basalt-fiber because the thermal conductivity of basalt-fiber, 0.8 W/m•K [13], is comparatively higher than that of foam glass, 0.115 W/m•K [14]. Thus, an increase in basalt-fiber addition results in an increase in thermal conductivity.…”
Section: Resultssupporting
confidence: 58%
“…In the sample with no added NC, the pores became larger as the sintering temperature increased. This occurred owing to the SO 3 → SO 2 + 1/2 O 2 reaction within the glass starting materials even when there was no C present, as observed in a previous study by Kim et al [10]. This has a bigger effect than the foam gas expansion caused by the C + O 2 → CO 2 reaction resulting from the carbon blowing agent, and it is believed that the inclusion of NC does not have a large effect until 4 wt%.…”
Section: Methodsmentioning
confidence: 60%
“…60 So, adding more BFs makes the thermal conductivity go up more than that of foam glass, which is 0.115 W/mK. 61 But a study found that adding steel fibers to concrete makes it better at transferring heat at temperatures up to about 700°C, with the most improvement at room temperature. This rise in thermal conductivity can be explained by the fact that steel has about 50 times more thermal conductivity than concrete.…”
Section: Thermal Conductivitymentioning
confidence: 99%